Textural characteristics, surface chemistry and activation of bleaching earth: A review - Hussin, F.; Aroua, M.K.; Daud, W.M.A.W. (Elsevier, 2011)
The unique properties of clay and clay minerals had made them valuable in the wide range of industrial applications. Low cost, local availability and effectiveness are the prevailing factors that have made clay and clay mineral to be used extensively as adsorbent in the purification of vegetable oils. The textural characteristics and surface chemistry play important roles in the bleaching earth performance. These two factors can be modified by various techniques including acid, basic, organic, thermal and pillaring activation. In these reviews, a comprehensive list of literatures on chemical and physical modification techniques of the bleaching earth was compiled and reviewed in relation to its effect on the structure, surface chemistry and adsorption capacity.